APPLYING ENGLISH SONGS METHOD IN VOCABULARY LEARNING AT SMAN 4 BAUBAU - Siki, Reni La (Jurnal Akademik FKIP Unidayan, 2023)
The problem statement in this research are How does the use of an English song help students in improving their vocabulary mastery?. The objective of this research determine whether students' vocabulary improves after listening to an English song at SMAN 4 Baubau and to define the process of employing songs to bold vocabulary knowledge at SMAN 4 Baubau. This researcher use Quasi-Experimental Research as design research, to be exact design pre-test and post-test. Study sort of this normal conducted by the instructors or a teacher who wants knowing is a strategy the effective or no with do multiple treatments. [1] stated study experimental is for allow researcher estimate influence something treatment experimental. The results of this research it can be concluded that English songs can improve students' vocabulary comprehension. There is a significant difference in the vocabulary understanding of students who are taught the English songs method and those who are not taught the English songs method. This is evidenced by the probability value (sig. (2-tailed)) which is smaller than then it can be stated as 0.000 < 0.05. This means that the null hypothesis (Ho) is rejected, while the alternative hypothesis (Ha) is accepted. In conclusion, teaching vocabulary comprehension with the English Songs method to the XI IPA 1 is better than XI IPA 2 which is taught without using the English songs method.